Event-triggered distributed voltage regulation by heterogeneous BESS in low-voltage distribution networks. (15th April 2022) - Kang, Wenfa; Chen, Minyou; Guan, Yajuan; Wei, Baoze; Vasquez Q., Juan C.; Guerrero, Josep M.
Abstract: High penetration level of PV sources in low-voltage distribution network (LVDN) leads to the voltage fluctuation problem, which may limit the maximal PV power generation due to the security issues of distribution networks. This paper proposes a distributed voltage regulation method by sharing the power of distributed heterogeneous battery energy storage systems (BESS) properly. With the help of local voltage/power droop controller, BESS absorbs power from LVDN when nodal voltage is above the upper limit, and injects power to LVDN when nodal voltage is lower than the bottom limit. The voltage regulation burden is properly shared among BESSs not only according to the capacities but also the state of charge (SoC). Moreover, even the communication network among BESSs is time-varying, the proposed method is able to regulate nodal voltages. For an extreme scenario with communication failures, the proposed method can also guarantee the voltage regulation and power sharing locally. Furthermore, a dynamic event-triggered communication strategy is designed for BESS aiming at reducing communication burden. Four simulation cases are designed on MATLAB/Simulink to validate the effectiveness of the proposed method. The results show that the proposed method is capable of maintaining nodal voltages within the normal range, and achieves the proportional regulation and SoC balance among different BESS with reduced communications. Highlights: Our research focuses on distributed voltage regulation in LVDN. A distributed event-triggered control method is proposed for BESS to share voltage regulation burden. BESS parameter differences, time-varying communication networks and communication link failures are investigated. A real-world LVDN validates the effectiveness of the proposed method.